Cohomology and formal deformations of n-Hom–Lie color algebras - Abdaoui, K.; Gharbi, R.; Mabrouk, S.; Makhlouf, A. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 512.5 The aim of this paper is to provide a cohomology of n-Hom–Lie color algebras, in particular, a cohomology governing one-parameter formal deformations. Then we also study formal deformations of the n-Hom–Lie color algebras and introduce the notion of Nijenhuis operator on a n-Hom–Lie color algebra, which may give rise to infinitesimally trivial (n-1)-order deformations. Furthermore, in connection with Nijenhuis operators, we introduce and discuss the notion of product structure on n-Hom–Lie color algebras.